Pemetaan Risiko Pekerja Konstruksi Berbasis Metode Job Safety Analysis Di PT BBB - Ali Zainal Abidin; Nina Aini Mahbubah (Fakultas Teknik, 2021)
The growing rapid infrastructure jobs have been acknowledged in line with rapid development of instfrastructure project in this nation. PT BBB is a prominent construction enterprise with specialize in both corporate and government project. As such project profoundly depend on human worker, a number of accident occurred which caused delay to finish scheduled task. This study aim to mapping degree of accident risk in order to mitigate risk likelihood. Job Safety Analysis is used as research approach. This research begun in determining working activities breakdown, followed by describing and identifing hazards in each working activity, and finally propose a mitigating scenario in order to eliminate work accidents. The results showed that there were 208 accidents. Those accidents have been calculated from seven working activities breakdown. Furthermore, it is found 22 potential hazards with likelihood risk as follow : 4 potential hazards is consideredaas low level risk, 8 potential hazards is determined in moderate level risk, 6 potential hazard is classified in high level risk and finally 4 potential hazards is considered as extreme level risk.